Analysis of Waste Utilization of Refuse Derived Fuel (RDF) Into Briquettes for Steam Power Electric Generation - Yossi Arif Rachman; Marhama Jelita (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
Waste in Indonesia reaches 65.2 million tons/year, dominated by organic and inorganic waste. Around 36% of the total waste has not been managed properly, including 4K1P waste (paper, wood, cloth, rubber, and plastic), which is flammable and can be made into RDF briquettes using the pyrolysis method and paraffin adhesive which will used three variations of raw materials, namely from organic, inorganic and mixed waste. The quality of the three briquettes was compared based on calorific value, ash content, water content, and PLTU fuel requirements if used as fuel for a 7.5 MW capacity PLTU. The weight of the initial raw material for briquettes is 2 kg which produces 875 grams of paper carbon charcoal, 648 grams of wood, 1.09 kg of plastic, 856 grams of cloth, and 1.16 kg of rubber, resulting in 10 pieces of organic, inorganic and mixed briquettes each. The test results show that inorganic briquettes have the best quality with a calorific value of 8,075.92 cal/g, water content of 1.75%, and ash content of 10.84%, where the calorific value and water content meet SNI-01-6235-2000. The minimum fuel requirement for a PLTU using RDF briquettes is inorganic briquettes, namely 3.05 tonnes/hour with an annual requirement of 26,205.6 tonnes/year. It can be concluded that inorganic briquettes have the best quality and require the least amount of fuel to be used in PLTU.